Development of cognitive model for analysis of technological complex of the dairy factory - Савчук, Ольга Вікторівна; Ладанюк, Анатолій Петрович (Technology audit and production reserves, 2015)
The expediency of cognitive modeling approaches to research and improve the management of complex systems. Identified dairy processing facility as a complex semistructured organizing technology system. For the study of systems of this class of methods to effectively use cognitive approach based on expert assessments, qualitative methods of analysis and fuzzy inference rules. On the basis of expert assessments, developed a fuzzy cognitive map of the complex functioning of the dairy and conducted its structural analysis. The studies prepared by the generalized static characteristics of the structure of the fuzzy cognitive map, such as consonances, dissonance and the influence of one factor on another. The findings are an initial step for the creation of an automated control system of technological complex dairy plant, and will be used to create resource management scenarios.